The Impact Of A Clinical Pathway On Treatment Outcomes Of Patients With Periodontitis In Public University Settings: A Quasi-experimental Study - Tuti Ningseh Mohd-Dom; Shahida Mohd-Said; Ooi Yow Hian; Siti Lailatul Akmar Zainuddin; Munirah Yaacob; Erni Noor; Aznida Firzah Abdul Aziz; Haslinda Ramli (Teikyo University School of Medicine, 2024)
Indexed by Scopus